2009
DOI: 10.1089/omi.2008.0085
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Changes in the Expression of Insulin Sensitivity-Related Genes after an Acute Load of Virgin Olive Oil

Abstract: Our aim was to examine whether an acute fat load could induce changes in the expression of insulin sensitivity-related genes in human peripheral blood mononuclear cells. Selection of candidate genes was based on previous studies with sustained virgin olive oil (VOO) consumption and biological plausibility in relation to insulin sensitivity. Eleven healthy volunteers ingested raw VOO (50 mL). Blood samples were collected at 0, 1 and 6 h. Plasma glucose, insulin and hydroxytyrosol increased at 1 h and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 49 publications
2
46
0
2
Order By: Relevance
“…This FC cut-off has been used in previous nutrigenomic studies [14,16]. The genes were identified and classified using Gene Ontology (GO) [17,18] and listed with gene names, FC, and p- values.…”
Section: Resultsmentioning
confidence: 99%
“…This FC cut-off has been used in previous nutrigenomic studies [14,16]. The genes were identified and classified using Gene Ontology (GO) [17,18] and listed with gene names, FC, and p- values.…”
Section: Resultsmentioning
confidence: 99%
“…Clear and consistent results from applying transcriptomics in human nutritional interventions have been obtained for the characterization of the molecular response to dietary lipids (PUFA, monounsaturated fatty acids (MUFA) and saturated fatty acids). In this regard, most experiments have targeted peripheral blood mononuclear cells [55][56][57][58][59] and a few others in adipose 60,61 and prostate 62 tissues. These studies have consistently shown that PUFA and MUFA repress the expression of proinflammatory genes, supporting the role of these nutrients as important modulators of cardiovascular disease risk.…”
Section: Transcriptomics: a Successful Approach To Characterize Nutrimentioning
confidence: 99%
“…45 A single dose of 50 mL of olive oil can elicit a rapid response of insulin sensitivity-related genes at postprandial time. 72 Insulin sensitivity after an olive oil-rich diet has been shown to be modulated by the polymorphism exon 1 variants of the scavenger receptor class B type I (SCARB1). 73 Recently, the mononuclear transcriptome response in human PBMCs after sustained VOO consumption (3 weeks) has been reported.…”
Section: Nutrigenomic Effectsmentioning
confidence: 99%